2018
DOI: 10.4274/tjh.2018.0127
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Adverse Effects of Prolonged Piperacillin-Tazobactam Use in Adults

Abstract: Objective:We aimed to find the incidence and risk factors of hematologic adverse effects of piperacillin-tazobactam (TZP).Materials and Methods:Adult patients who used TZP for more than 10 days were included in the study.Results:The incidence of leukopenia, neutropenia, and eosinophilia in 110 TZP therapy episodes was found to be 16.3%, 10%, and 10%, respectively. Lower Charlson Comorbidity Index score, lower initial leukocyte count, combination of TZP with another antibiotic, and total duration of TZP therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The incidence of piperacillin-induced neutropenia varies from 10% to 34% in studies assessing a minimum duration of 10 days of therapy. 5,39 However, the exceptionally high incidence of 34% is limited by the retrospective nature of the corresponding study, which included a small cohort of patients treated for osteomyelitis and used a conservative threshold of <2.0 × 10 3 /µL for neutropenia. 5 Piperacillin-induced neutropenia in adults treated with shorter courses is rare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of piperacillin-induced neutropenia varies from 10% to 34% in studies assessing a minimum duration of 10 days of therapy. 5,39 However, the exceptionally high incidence of 34% is limited by the retrospective nature of the corresponding study, which included a small cohort of patients treated for osteomyelitis and used a conservative threshold of <2.0 × 10 3 /µL for neutropenia. 5 Piperacillin-induced neutropenia in adults treated with shorter courses is rare.…”
Section: Resultsmentioning
confidence: 99%
“…1,3 Piperacillin, a member of the ureidopenicillin subclass, has been implicated in β-lactam-induced neutropenia more often than any other agent, with 246 cases. 2,3,5,29,31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Cases involving piperacillin or piperacillin-tazobactam were included in this count. Notably, a systematic review of piperacillin or piperacillin-tazobactam-induced neutropenia identified 183 cases using the Food and Drug Administration Adverse Event Reporting System.…”
Section: Incidence and Characteristicsmentioning
confidence: 99%
“…Numerous studies have reported that the duration of treatment is directly associated with linezolid-associated thrombocytopenia 19,20 . Benli et al found that the incidence of leukopenia was 10% in patients treated with piperacillin-tazobactam for longer than 10 days 21 . In our study, it was found that as the days of antibiotic exposure increased, the frequency of observed side effects significantly increased, which aligns with the limited data available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the exact incidence of PTZ-induced haematological adverse effects varied between cohort studies due to the difficulty of definite diagnosis in clinical practice. Studies have merely indicated the risk factors for PTZ-induced haematological adverse effects as prolonged courses and increased cumulative doses 4 5…”
Section: Discussionmentioning
confidence: 99%